2011
DOI: 10.1680/coma.900040
|View full text |Cite
|
Sign up to set email alerts
|

Early-age properties of concrete: overview of fundamental concepts and state-of-the-art research

Abstract: The long-term performance of concrete structures is affected to a large extent by the properties and behaviour of concrete at early age. However, the fundamental mechanisms affecting the early-age behaviour of concrete have not yet been fully understood. This is due to the various highly interrelated factors influencing it, and the complexity of testing techniques needed for its investigation. With modern developments in concrete technology, it has become essential to evaluate the influence of these interrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 72 publications
(105 reference statements)
1
25
0
Order By: Relevance
“…This behavior was attributed to the addition of nTiO2 into the cementitious materials, which resulted in an accelerated rate of hydration process. A similar attribute has been reported in previous studies that when nTiO2 is uniformly distributed throughout the matrix, the hydration process and formation of C-S-H gel is accelerated, which results in early strength [32,[47][48]. In the other set of mixes, the effect of nTiO2 inclusion on the compressive strength of mixes was investigated after a different curing time.…”
Section: Compressive Strengthsupporting
confidence: 78%
“…This behavior was attributed to the addition of nTiO2 into the cementitious materials, which resulted in an accelerated rate of hydration process. A similar attribute has been reported in previous studies that when nTiO2 is uniformly distributed throughout the matrix, the hydration process and formation of C-S-H gel is accelerated, which results in early strength [32,[47][48]. In the other set of mixes, the effect of nTiO2 inclusion on the compressive strength of mixes was investigated after a different curing time.…”
Section: Compressive Strengthsupporting
confidence: 78%
“…This may be due to (1) OC has good adsorption of heavy metals and better adsorption of organic compounds than the IOCs used in this study, (Table 4 and Fig. 4) therefore less organic pollutants were able to be inhibit the hydration process; (2) Bayat et al [21] and Teerawattanasuk and Voottipruex [22] reported that the shear and yield strength increased when the content of bentonite increased, which can act as plastic fines; (3) the IOCs slurries increased the water content, which decreased the strength development [23]. When comparing P-2IOC1 with P-IOC1, it was found that doubling the IOC1 content reduced the strength to half at 28 days.…”
Section: Ucsmentioning
confidence: 70%
“…We also found that the age of concrete at the time of the test did not significantly affect the elastic modulus. Especially for the UHPC-2 and UHPC-3 mixtures, the elastic modulus at 7 and 28 days were almost equal, as shown in Table 10, because the elastic modulus of concrete during the early stages develops rapidly compared to compressive strength [38]. Myers also pointed out that about 90% or more of the elastic modulus value is achieved within the first 24 h after casting [39].…”
Section: Compressive Strength Of Concrete At Room Temperaturementioning
confidence: 99%